1996
DOI: 10.1083/jcb.134.5.1179
|View full text |Cite
|
Sign up to set email alerts
|

Two muscle-specific LIM proteins in Drosophila.

Abstract: Abstract. The LIM domain defines a zinc-binding motif found in a growing number of eukaryotic proteins that regulate cell growth and differentiation during development

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(97 citation statements)
references
References 47 publications
2
95
0
Order By: Relevance
“…This gene was suggested to have a role in the maintenance of cytosolic Ca 2+ levels, which may become raised as part of the stress response. Transcripts for a gene with 94% identity at the amino acid level to D. melanogaster LIM protein (Stronach et al 1996) were found in the goldenrod gall moth E. scudderiana after exposure to low temperatures (Bilgen at al 2001). Muscle LIM proteins are essential for myogenesis and promote differentiation of striated muscle (Arber et al 1994).…”
Section: Mitochondrial Degradationmentioning
confidence: 99%
“…This gene was suggested to have a role in the maintenance of cytosolic Ca 2+ levels, which may become raised as part of the stress response. Transcripts for a gene with 94% identity at the amino acid level to D. melanogaster LIM protein (Stronach et al 1996) were found in the goldenrod gall moth E. scudderiana after exposure to low temperatures (Bilgen at al 2001). Muscle LIM proteins are essential for myogenesis and promote differentiation of striated muscle (Arber et al 1994).…”
Section: Mitochondrial Degradationmentioning
confidence: 99%
“…In situ hybridization to embryos was performed as described (Stronach et al 1996). The dpp antisense riboprobe, corresponding to dpp coding sequence, was generated by use of the Boehringer Mannheim Genius RNA labeling kit according to the manufacturer.…”
Section: Staining and Imagingmentioning
confidence: 99%
“…MLP in vertebrates also initiates a stretchregulated downstream response, a hypertrophic program that leads to an increase in the number of sarcomeres, likely through its ability to translocate from the Z-disk to the nucleus, where it associates with muscle-specific transcriptional activators (Arber et al, 1994;Knöll et al, 2002). In contrast, Drosophila Mlp(s) display some transient nuclear localization, but with no proven nuclear function, because an Mlp84B transgene carrying a nuclear export signal can fully rescue the pupal lethality of mlp84B mutants (Stronach et al, 1996;Clark et al, 2007).…”
Section: The Z-disk As a Focal Point For Force Propagationmentioning
confidence: 99%
“…1). The Drosophila MLP family is encoded by two genes, mlp60A and mlp84B, and their protein products are both detected at the periphery of Z-disks and at myotendinous junctions (Stronach et al, 1996;Clark et al, 2007). Interestingly, despite its early localization, Mlp84B depletion results in late muscle defects observed just before pupation.…”
Section: The Z-disk As a Focal Point For Force Propagationmentioning
confidence: 99%